Forty-five Techniques Every Counselor Should Know ; GSC002289, GSC002290 - Erford, Bradley T. (Hoboken : Pearson Education, Inc., 2020)
"A user-friendly guide to essential counseling techniques and skills. Concise, yet thorough, 45 Techniques Every Counselor Should Know is designed to prepare students to enter their field with sound ideas for applying theory-based techniques to their counseling. Coverage of each technique starts with the presentation of the theoretical origins, then provides a step-by-step guide to implementation, and culminates with opportunities for application. Transcriptions, case examples, multicultural implications, and outcomes-based research demonstrate real-life application of how the techniques can be used in counseling practice. This indispensable resource provides hands-on help for working with clients from all backgrounds to create positive changes in their lives and meet their counseling goals. The 3rd Edition features new case studies and application questions and five new techniques detailed in new chapters on Mindfulness Meditation (Ch. 17); Assigning Homework (Ch. 29); Narrative Theory (Ch. 43); Strengths-Based Counseling (Ch. 44); and Client Advocacy (Ch. 45)."--Amazon.com.
Includes bibliographical references (pages 286-306) and index.
Keywords: Applied Psychology; Cognitive-Behavioral Techniques; Core Counselling Skills; Person-Centered Techniques; Solution Focused Techniques; Narrative Therapy Techniques; Mindfulness and Emotion Regulation; Motivational Interviewing Techniques; Creative and Experiential Techniques; Counseling psychology; Psychotherapy; Counselling Techniques